The factors contributing to the housing ownership among youth household in Melaka - Mohamed Osman, Mariana; Ramlee, Muhammad Adib; Ab Rahman, Syakir Amir; Ibrahim, Mansor (2017)
Homeownership has been the ultimate goal of every human being worldwide. The needs of the housing can be considered a necessity to the human being, to shelter and safeguard themselves for privacy as well as any dangers that can affect their life beings. Therefore the housing ownership issue has become one of the major problems that are faced by all, either in developing or developed countries especially for the young generation, with the current situation the housing price is getting expensive. Hence the youth household is the one who highly impacted by the rising prices. Therefore, the aim of this paper is to address what are the contributing factors to the housing among youth household to own a house especially in the urban area in the case study of the state of Melaka.